The training module concept: a way towards quality improvement and inclusion in German Vocational Education and Training (VET)? - Grebe, Tim [Verfasser]; Ekert, Stefan [Verfasser] (My University, 2017)
"VET in Germany is based on a dual system (learning in vocational schools and companies) within regulated training occupations. It leads to a professional degree in the respective training occupation that recognize countrywide. Traditionally, dual VET does not have a modularize structure. The German Federal Institute of Vocational Education and Training (BIBB) has recently developed competence-oriented training modules ("Ausbildungsbausteine") for selected training occupations. These training modules have the aim of making learning outcomes more transparent and comparable, and of increasing the quality of qualification measures in prevocational training. The latter aims at easing transitions from these measures into regular (dual) VET. The training modules have been implemented in selected regions and qualification measures within JOBSTARTER CONNECT, a pilot programme funded by the Federal Government and the European Social Fund (ESF). This article summarizes the main of the external evaluation of the programme." (Authors' abstract ; BIBB-Doku)
Keywords: S 1.3.1 Ausbildung im Dualen System; S 2.3.2 Programme in der Berufsbildung; L 6.2.3 Evaluation; L 1.1.3 Modulorientierung; Berufsbildung; Duales System; JOBSTARTER; Modularisierung; Ausbildungsbaustein; Evaluation; Lernfeld